An innovative approach to teaching endodontics in the preclinical stage of the dental education (Эндодонтия Today)
The present study aimed at the development of an endodontic simulation model, able to implement the electronic method of working length determination (EAL) in a setting of undergraduate learning. The development of the simulation model was accompanied by several investigations, helping to assess products’ potential and aiming to create the sound scientific basis for its future implementation as a learning tool. This investigation was conducted in the framework of the regular phantom-lab course. During the initial implementation 450 student have been trained. The models’ capability to imitate clinical conditions was investigated by means of radiographic, macrophotograpic and CAD/CAM techniques. The EAL-features of the present model allowed not only for precise determination of apical constriction (R²=0,0198) versus radiographic method (R² = 0,0019), but also granted a precise preparation of the apical constriction in the vast majority of cases (up to 83%).